Inhibition of diabetic nephropathy by a decoy peptide corresponding to the “handle” region for nonproteolytic activation of prorenin - Ichihara, Atsuhiro; Hayashi, Matsuhiko; Kaneshiro, Yuki; Suzuki, Fumiaki; Nakagawa, Tsutomu; Tada, Yuko; Koura, Yukako; Nishiyama, Akira; Okada, Hirokazu; Uddin, M. Nasir; Nabi, A.H.M. Nurun; Ishida, Yuichi; et al. (The Journal of Clinical Investigation, 2004)
We found that when a site-specific binding protein interacts with the “handle” region of the prorenin prosegment, the prorenin molecule undergoes a conformational change to its enzymatically active state. This nonproteolytic activation is completely blocked by a decoy peptide with the handle region structure, which competitively binds to such a binding protein. Given increased plasma prorenin in diabetes, we examined the hypothesis that the nonproteolytic activation of prorenin plays a significant role in diabetic organ damage. Streptozotocin-induced diabetic rats were treated with subcutaneous administration of handle region peptide. Metabolic and renal histological changes and the renin-Ang system components in the plasma and kidneys were determined at 8, 16, and 24 weeks following streptozotocin treatment. Kidneys of diabetic rats contained increased Ang I and II without any changes in renin, Ang-converting enzyme, or angiotensinogen synthesis. Treatment with the handle region peptide decreased the renal content of Ang I and II, however, and completely inhibited the development of diabetic nephropathy without affecting hyperglycemia. We propose that the nonproteolytic activation of prorenin may be a significant mechanism of diabetic nephropathy. The mechanism and substances causing nonproteolytic activation of prorenin may serve as important therapeutic targets for the prevention of diabetic organ damage.